Genetic Architecture and Genomic Prediction of Cooking Time in Common Bean (Phaseolus vulgaris L.) - Diaz, Santiago; Ariza-Suarez, Daniel; Ramdeen, Raisa; Aparicio, Johan; Arunachalam, Nirmala; Hernandez, Carlos; Diaz, Harold; Ruiz, Henry; Piepho, Hans-Peter; Raatz, Bodo (Frontiers in Plant Science, 2021)
Cooking time of common bean is an important trait for consumer preference, with implications for nutrition, health and environment. For efficient germplasm improvement breeders need more information on the genetics, to identify fast cooking sources with good agronomic properties, and molecular breeding tools. In this study we investigated a broad genetic variation among tropical germplasm from both Andean and Mesoamerican genepools. Four populations were evaluated for cooking time (CKT), water absorption capacity (WAC) and seed weight (SdW): a bi-parental RIL population (DxG), an 8-parental Mesoamerican MAGIC population, and an Andean (VEF) and a Mesoamerican (MIP) breeding line panel. A total number of 922 lines were evaluated in this study. Significant genetic variation was found in all populations with high heritabilities, ranging from 0.64 to 0.89 for CKT. CKT was linked to seed coat color, with white colored seed cooking fastest. Marker trait associations were investigated by QTL analysis and GWAS, resulting in the identification of 10 QTL. In populations with Andean germplasm, an inverse correlation of CKT and WAC was observed, also a QTL on Pv03 that inversely controls CKT and WAC (CKT3.2/WAC3.1). WAC7.1 was found in both Mesoamerican populations. QTL only explained a small part of the variance and phenotypic histograms support a more quantitative mode of inheritance. For this reason, we evaluated how genomic prediction (GP) models can capture the genetic variation. GP accuracies for CKT varied, ranging from good results for the MAGIC population (0.55) lower accuracies in the MIP panel (0.22). The phenotypic characterization of parental material will allow for the cooking time trait to be implemented in the active germplasm improvement programs. Molecular breeding tools can be developed to employ marker assisted selection or genomic selection, which looks to be a promising tool in some populations to increase the efficiency of breeding activities.